The School Dropout: Causes and Effects in University Education - Bonilla-Jurado, Diego (2023)
The objective of the research is to review the most recent topics about the associated determining factors related to university dropout. University abandonment is considered, by most university institutions, as a phenomenon that threatens the prospecting of education and society in general. The research is qualitative and descriptive. Based on the hermeneutics of recent works, with the determination to review what is currently being done with the main theme of the study. The type of article is for review, which, without being original, collects a series of relevant and current information on the thematic axes. The results of the study allowed us to know, identify and analyze the different causes by which the phenomenon of university dropout is activated and even, take into consideration positions from other countries which allowed us to reach relevant dissertations. The conclusions of the research, in addition to knowing the determining factors associated with attrition, also allow us to issue some recommendations to university institutions, to reduce the dropout rate and be able to counteract the social consequences that it entails.